2022
DOI: 10.1101/2022.06.20.494087
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Platform Proteomic Analysis of Alzheimer’s Disease Cerebrospinal Fluid and Plasma Reveals Network Biomarkers Associated with Proteostasis and the Matrisome

Abstract: Robust and accessible biomarkers that can capture the heterogeneity of Alzheimer’s disease and its diverse pathological processes are urgently needed. Here, we undertook an investigation of Alzheimer’s disease cerebrospinal fluid (CSF) and plasma from the same subjects using three different proteomic platforms—SomaLogic SomaScan, Olink proximity extension assay, and tandem mass tag-based mass spectrometry—to assess which protein markers in these two biofluids may serve as reliable biomarkers of AD pathophysiol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 42 publications
(81 reference statements)
5
22
0
Order By: Relevance
“…Recently, our mechanistic study of inflammation control revealed that constitutively active G9a is the upstream regulator of METTL3/m 6 A-mediated translation in chronically inflamed macrophages that mimic AD-related neuroinflammation 18 . In agreement with findings that translational regulation was broadly perturbed in various neurodegenerative diseases, 19,20,21 and loss of proteostasis is an AD hallmark, 22,23 our in vivo ChaC-MS identification of G9a interactions with translation regulators such as METTL3 revealed a new, noncanonical function of G9a in the translational or posttranslational regulation of AD pathogenesis. Because translational mechanisms ultimately determine function-related protein abundance or modification states 24 , we developed a new mechanism-based therapeutic for AD, i.e., MS1262, a brain-penetrant inhibitor of G9a, to block G9a-mediated translation of AD-related proteins.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, our mechanistic study of inflammation control revealed that constitutively active G9a is the upstream regulator of METTL3/m 6 A-mediated translation in chronically inflamed macrophages that mimic AD-related neuroinflammation 18 . In agreement with findings that translational regulation was broadly perturbed in various neurodegenerative diseases, 19,20,21 and loss of proteostasis is an AD hallmark, 22,23 our in vivo ChaC-MS identification of G9a interactions with translation regulators such as METTL3 revealed a new, noncanonical function of G9a in the translational or posttranslational regulation of AD pathogenesis. Because translational mechanisms ultimately determine function-related protein abundance or modification states 24 , we developed a new mechanism-based therapeutic for AD, i.e., MS1262, a brain-penetrant inhibitor of G9a, to block G9a-mediated translation of AD-related proteins.…”
Section: Introductionsupporting
confidence: 89%
“…6B). For example, the level of SPARC-related modular calcium-binding protein 1 (SMOC1), an Aβ plaque-associated synaptic protein 23,107 was found elevated in AD CSF nearly 30 years before the onset of symptoms 28 . Other CSF markers 28 showing MS1262 affected/reversed expression included the following (Fig.…”
Section: Ms1262 Reversed Protein Expressions or Phosphorylation That ...mentioning
confidence: 99%
“…Significant correlations of these peptides to the established biomarker and cognitive measures indicate the potential of these measurements to classify or stage disease progression. The targeted SRM measurement correlations largely agree with those observed from unbiased discovery proteomics 43 and parallel reaction monitoring 23 experiments.…”
Section: Usage Notessupporting
confidence: 73%
“…The comparison of existing biomarkers to the SRM peptide measurements can be accomplished by correlation, where the degree of correlation indicates how similar a peptide measurement is to the established immunoassay-measured biomarkers of Aβ(1-42), total Tau, and pTau as well as cognition (MoCA score). In Figure 6A, we demonstrate that 57 of the 58 The targeted SRM measurement correlations largely agree with those observed from unbiased discovery proteomics 43 and parallel reaction monitoring 23 experiments.…”
Section: Use Case 5: Correlation Of Peptide Biomarker Abundance To Aβ...supporting
confidence: 62%
See 1 more Smart Citation